RETRACTED: The effect of biosynthesized silver nanoparticles on Pseudomonas aeruginosa-infected dogs wounds - Ali Hussein Aldujaily; Kifah Fadhil Hassoon; Abdulameer Abid Hatem; Murtadha Abbas (PLoS ONE, 2025)
Environmental factors such as lesion and bacterial infection risk affect wound healing. Many researchers are interested in silver nanoparticles (AgNPs) due to their anti-inflammatory, antibacterial, and wound-healing properties. This study compared AgNPs to Amikacin on dogs’ P. aeruginosa -infected wounds. Sixteen dogs were divided into four groups of four and received costo-abdominal right-side full-thickness skin wounds. Thereafter, a bacterial suspension was administered to each wound bed. To assess wound infection, a complete bacterial load count was performed. Clinical wound healing assessments were done (healing rate (%), healing time (days), and comparisons between AgNPs and Amikacin were made to determine their antibacterial actions, as well as histological examination of the skin. Tribulus terrestris was used for the biosynthesis of AgNPs in this study. The AgNPs were characterized using UV-vis spectroscopy, SEM, XRD, EDS, AFM and zeta potential. AgNPs, AgNPs-Amikacin, Amikacin, or no treatment (control group) were topically administered to the wound bed. AgNPs cure wounds in 20 ±  1.64 days, while Amikacin takes 28 ±  1.75. In comparison to amikacin, AgNPs 18 ±  1.47 healed the fastest. AgNPs-Amikacin, AgNPs, and Amikacin can eradicate P. aeruginosa -infected wounds in 7, 9, and 14 days, according to bacterial counts. AgNPs reduce inflammation and increase collagen fiber deposition to treat skin lesions. AgNPs also reduced hemorrhagic areas and inflammatory cells in P. aeruginosa -infected wounds, aiding wound healing. All in all, these nanoparticles reduced bacterial wound infections and aided tissue healing. It has been found that AgNPs can be used as an efficacious antimicrobial and anti-inflammatory agent in wound healing instead of antibiotics.